2022
DOI: 10.1186/s12912-022-00984-1
|View full text |Cite
|
Sign up to set email alerts
|

Difference between self-reported adherence to standard precautions and surveillance and factors influencing observed adherence: a quantile regression approach

Abstract: Background Standard precautions are minimum healthcare-associated infection prevention practices applied in all healthcare settings. The aim of this study was to investigate adherence to standard precautions using a survey and surveillance. Factors affecting observed adherence to standard precautions were also determined. Methods This cross-sectional observational study included 163 clinical nurses who were directly involved in patient care. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…However, nurses from some Asian countries adhere to and comply with SPs suboptimally. For instance, suboptimal compliance of nurses was reported in Hong Kong (46%; Wong et al, 2021), Malaysia (63.7%; Mohamad et al, 2022), the Philippines (78.2%; Berdida, 2023), and Singapore (76.68%; Lim et al, 2021), while poor adherence to SPs in South Korea (Kim & Lee, 2022). Similarly, a…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, nurses from some Asian countries adhere to and comply with SPs suboptimally. For instance, suboptimal compliance of nurses was reported in Hong Kong (46%; Wong et al, 2021), Malaysia (63.7%; Mohamad et al, 2022), the Philippines (78.2%; Berdida, 2023), and Singapore (76.68%; Lim et al, 2021), while poor adherence to SPs in South Korea (Kim & Lee, 2022). Similarly, a…”
Section: Introductionmentioning
confidence: 98%
“…However, nurses from some Asian countries adhere to and comply with SPs suboptimally. For instance, suboptimal compliance of nurses was reported in Hong Kong (46%; Wong et al., 2021), Malaysia (63.7%; Mohamad et al., 2022), the Philippines (78.2%; Berdida, 2023), and Singapore (76.68%; Lim et al., 2021), while poor adherence to SPs in South Korea (Kim & Lee, 2022). Similarly, a scoping review of 17 studies (McCauley et al., 2021) discovered that missed nursing care during infection prevention and control is the same as noncompliance with infection prevention and control guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, healthcare workers' compliance with infection control and prevention was low during patient care (54%) and invasive procedures (46%) (Wong et al, 2021), while Malaysian healthcare workers' compliance was 63.7% (Mohamad et al, 2022). South Korean nurses reported a 76.8% observed adherence to SPs (Kim & Lee, 2022). Similarly, suboptimal compliance with SPs was reported among nurses in Brazil (69.4%), Hong Kong (57.45%) (Pereira et al, 2015), and Singapore (76.68%) (Lim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It can be performed by observation, surveillance, and selfadministered surveys. One study found that the percentage of compliance by observation was 76.8%, while in a survey, it was 95% in the same participants (8). According to the WHO, observation is the gold standard for evaluation (12).…”
Section: Discussionmentioning
confidence: 99%